Pengaruh Tata Ruang Perpustakaan Sekolah Terhadap Minat Baca Siswa SMPN 1 Kecamatan Paguyaman Pantai Kabupaten Boalemo. - Malatani, Rosita; Hafid, Radia; Mahmud, Melizubaida; Sudirman, Sudirman; Koniyo, Rierind (Journal of Economic and Business Education, 2024)
This study uses a quantitative approach. The data collection methods used in this research are observation, questionnaires and documentation. The population in this study were all students of SMP Negeri 1 Paguyaman Paantai Discrict, totaling 85 students, while the sample in this study was 15 students. The analytical method used is simple linear regression. The research results show that there is a positive and significant influence between library spatial planning on stuedents’ reading interest. A comparison of the calculated t value which is greater than the t tabel shows that the research has a positive and significant effect. Then the results of the coefficient test showed a value of 0.332, which means 33.2% of the Reading Interest variable is explained by the Library Spatial Planning variable. In other words, the higher the library layout, the higher the students’ reading interest.